Development of Personal Mobility Solution “Motorised Shoes” - Abdul Aziz, Muhammad Asyraf (IRC, 2019)

(untitled)
For the past decades, public transportation has distinguished themselves as reliable mode of transportation especially in urban areas within the emergence of increasing traffic congestions rapidly happening from time to time. The demand for smooth efficient transportation had been on the incline due to increasing urban community dependencies toward public transportation compared to other alternatives such as self-owned vehicle. This study identifies critical challenges associated with the last mile solution in our crowded city. Last mile solution models adopted in developed nations were evaluated and the identified best practices contributed to its end merits. By taking account of accumulated merits of each model, composite ideas gathered will be further factored into our own proposed idea of last mile solution. The study further considered any of the environmental impacts of the proposed idea, adding its feasibility in operating based on stated environment, crowded urban-city areas. Solution-wise, the relevancies of this last mile solution are backed under its achievable construction, applications and lastly, city community approvals of it itself.